Tadaa Box - Azmi, Nurul Athirah; Ismail, Nurul Fasila; Che Di, Siti Aisyah; Othman, Nur Farhanah; Mohd Zuri, Nojie Asyikin; Selamat, Nordibradini (Universiti Teknologi MARA, Kedah, 2018)
TADAA Box is multifunction box equipped with mini activities that support teaching and learning process such as ABD, 123, shapes, animals, and colours. This box will be filled with colourful and bright colours in order to capture and attract children‟s attention and interest.